Antiviral Activities of Interleukin-27: A Partner for Interferons? - Amsden, Heather; Kourko, Olena; Roth, Madison; Gee, Katrina (Frontiers in Immunology, 2022)
Emergence of new, pandemic-level viral threats has brought to the forefront the importance of viral immunology and continued improvement of antiviral therapies. Interleukin-27 (IL-27) is a pleiotropic cytokine that regulates both innate and adaptive immune responses. Accumulating evidence has revealed potent antiviral activities of IL-27 against numerous viruses, including HIV, influenza, HBV and more. IL-27 contributes to the immune response against viruses indirectly by increasing production of interferons (IFNs) which have various antiviral effects. Additionally, IL-27 can directly interfere with viral infection both by acting similarly to an IFN itself and by modulating the differentiation and function of various immune cells. This review discusses the IFN-dependent and IFN-independent antiviral mechanisms of IL-27 and highlight the potential of IL-27 as a therapeutic cytokine for viral infection.